O Comitê de Bacias Hidrográficas dos rios Aguapeí e Peixe e seus municípios: uma proposta de legislação municipal complementar de proteção de recursos hídricos - Marques, Mário César Vieira [UNESP] (2014)
Brazilian municipalities have their water resources protected only by state and federal laws; therefore, they do not meet specific needs and particularities of local environmental interests. The objective of this study is to establish a plan to adopt a complementary law of use and occupation of the soil aiming the protection and integrated management of water resources for municipalities that are members of the Aguapeí-Peixe Watershed Committee (CBH-AP). The approval of municipal laws may consolidate a network of laws protecting the water resources in the basin from each participating municipality. As it is a work proposal that involves different interests, expectations, roles and skills, and the participation of professionals with very different profiles, some actions should be taken in order to ensure its effectiveness with several steps involving short, medium and long-term targets. The methodology included a comparative study of existing laws in many municipalities which have adopted laws dealing with water resources in the state of São Paulo; the development of a comprehensive law prototype to guide and subsidize municipalities to develop their specific legislation, and political discussions for municipalities to join the process of execution of the laws in the CBH-AP municipalities. A program to promote, discuss and debate via CBH Technical Chambers this proposal with representatives of the municipalities concerned was developed. These representatives will make the necessary adjustments together with the local communities... (Complete abstract click electronic access below)